Yearbook of physical anthropology - American Association of Physical Anthropologists (Washington, D.C. : American Association of Physical Anthropologists, 1945)
Vol. 9 called also: Physical anthropology 1953-1961.
Biological abstracts
Publication suspended 1953-61 and 1968-71.
Vols. for 1980- issued as supplement to: American journal of physical anthropology.
Description based on: Volume 1 (1945); title from cover.
Latest issue consulted: Volume 59 (2015).
Keywords: Physical anthropology -- Periodicals; Physical anthropology; Anthropology, Physical; Periodicals; Periodicals